A combination index and glycoproteomics-based approach revealed synergistic anticancer effects of curcuminoids of turmeric against prostate cancer PC3 cells. (1st March 2021) - Wei, Meng-Meng; Zhao, Shu-Juan; Dong, Xue-Man; Wang, Yong-Jie; Fang, Can; Wu, Pu; Song, Gao-Qian; Gao, Jun-Na; Huang, Zhi-Hui; Xie, Tian; Zhou, Jian-Liang
Abstract: Ethnopharmacological relevance: Herbal medicines (HMs) often exert integration effects, including synergistic, additive and antagonistic effects, in such ways that they act on multiple targets and multiple pathways on account of their multiple components. Turmeric, made from the rhizome of Curcuma longa L., is a well-known HM prescribed in the polyherbal formulas for cancer treatment in traditional Chinese medicines (TCMs). However, neither the multiple anticancer compounds of turmeric nor the integration effects of these components are fully known. Aim of the study: This work aims to develop a systematic approach to reveal the integration effect mechanisms of multiple anticancer compounds in turmeric against prostate cancer PC3 cells. Materials and methods: Combination index and omics technologies were applied to profile the integration effect mechanisms of bioactive compounds in proportions naturally found in turmeric. PC3 cell line (a prostate cancer cell line) fishing and high resolution mass spectrometry were employed to screen and identify the anticancer compounds from turmeric. The combinations which contain different cell-bound compounds in natural proportions were prepared for further evaluation of anti-cancer activity by using cell viability assays, and assessment of cell apoptosis and cell cycle analysis. Combination index analysis was applied to study the integration effects of the anticancer compounds in their natural proportions. Finally, quantitative glycoproteomics/proteomics and Western blot were implemented to reveal the potential synergistic effect mechanisms of the anticancer compounds based on their natural proportions in turmeric. Results: Three curcuminoids (curcumin, CUR; demethoxycurcumin, DMC; bisdemethoxycurcumin, BDMC) in turmeric were discovered and shown to possess significant synergistic anticancer activities. Combination index analysis revealed an additive effect of CUR combined with DMC or BDMC and a slight synergistic effect of DMC combined with BDMC in natural proportions in turmeric, while a combination of all three curcuminoids (CUR, DMC and BDMC) at a ratio of 1:1:1 yielded superior synergistic effects. Interestingly, the presence of BDMC and DMC are essential for synergistic effect. Glycoproteomics and proteomics demonstrated that different curcuminoids regulate various protein pathways, such as ribosome, glycolysis/gluconeogenesis, biosynthesis of amino acids, and combination of CUR + DMC + BDMC showed the most powerful effects on down-regulation of protein expression. Conclusions: Our analytical approach provides a systematic understanding of the holistic activity and integration effects of the anti-cancer compounds in turmeric and three curcuminoids of turmeric showed a synergistic effect on PC3 cells. Graphical abstract: Image 1 Highlights: A combination index and glycoproteomics-based approach was proposed for integration effects profiling of curcuminoids. Three curcuminoids in turmeric were proved to possess significant synergetic anticancer activities against PC3 cells. BDMC and DMC are essential for these active compounds to obtain the synergistic effect against PC3 cells. The combination of CUR + DMC + BDMC showed the most powerful on down-regulation of the protein expression.